Ancient builders of the Amazon [videorecording (DVD)] - Townsley, Graham; Galindo, Eileen (PBS, 2023)
Recent stunning discoveries are exploding the myth of the Amazon as a primeval wilderness, revealing traces of ancient civilizations that flourished there for centuries. Dense settlements indicate populations in the millions, supported by sophisticated agricultural systems, while huge geometric earthworks and roadways bear witness to complex religious ideas and social networks.